Destructive Pneumonia In Children: Complex Issues Of Diagnosis And Choice Of Individual Etiopathogenetic Therapy (Eurasian Medical Research Periodical, 2024)
A review of literature data on the issues of diagnosis and selection of individual etiopathogenetic therapy for destructive pneumonia in children was carried out. The most common classifications and regulatory documents describing the procedure for diagnosis and choice of therapy for this pathology are presented. The main pathogens and means of antibacterial therapy necessary for treatment are characterized. A clinical case is described demonstrating diagnostic and therapeutic approaches for destructive pneumonia